Qualitative and quantitative phytochemical composition, antimicrobial activity, and brine shrimp cytotoxicity of different solvent extracts of Acanthus polystachyus, Keetia gueinzii, and Rhynchosia elegans - James Kiamba Mailu; Joseph Mwanzia Nguta; James Mucunu Mbaria; Mitchel Otieno Okumu (SpringerOpen, 2021)
Abstract Background The root, root bark, and root tubers of Acanthus polystachyus, Keetia gueinzii, and Rhynchosia elegans are used for managing bacterial and fungal infections among the Luo community of Kisumu East Sub County in Kenya. However, data on the efficacy of these plants against common bacterial and fungal pathogens is not available. The safety of these plants is also not known. This study aimed to investigate the phytochemical composition, antimicrobial properties, and safety of different solvent extracts of the roots, root barks, and root tubers of Acanthus polystachyus, Keetia gueinzii, and Rhynchosia elegans. The broth microdilution method evaluated the antimicrobial activities of the root, root bark, and root tuber extracts (water, acetone, and methanol) of Acanthus polystachyus, Keetia gueinzii, and Rhynchosia elegans. Gram-positive (Bacillus cereus, Staphylococcus aureus), gram-negative (Escherichia coli), and fungal (Candida albicans) microorganisms were used in the evaluation. The safety of the extracts was evaluated in Artemia salina. The phytochemical composition of the extracts was determined using qualitative and quantitative assays. Results In general, the extracts of Acanthus polystachyus, Keetia gueinzii, and Rhynchosia elegans displayed poor antimicrobial properties relative to conventional antimicrobial agents including Amoxicillin, Gentamicin, and Nystatin. The aqueous extract of Acanthus polystachyus and the aqueous, acetone, and methanol extracts of Keetia gueinzii were safe in Artemia salina but all other extracts were cytotoxic to Artemia salina. Conclusions These findings suggest that the use of the roots, root barks, and root tubers of Acanthus polystachyus, Keetia gueinzii, and Rhynchosia elegans is limited by poor antimicrobial efficacy and cytotoxicity.